Stroke rates corresponding to critical speed and the maximal speed of 30 min in swimmers of different training status - Greco, C.; Pelarigo, J.; Perandini, L.; Figueira, T.; Denadai, B. (Biomechanics and Medicine in Swimming X, 2006)
The objective of this study was to verify the effect of aerobic performance level on the relationship between stroke rates at critical speed (SRCS) and at maximal speed of 30 min (SRS30). Twenty-three male swimmers of 15 to 20 yr were divided by aerobic performance level (S30) into G1 (n = 10) and G2 (n = 13) groups. SRCS was determined by the slope of the regression line between the number of stroke cycles and time. SRS30 was determined trough the mean value of stroke rate obtained during 30 min test. CS was higher than S30 in G1 (1.30 ± 0.04 and 1.23 ± 0.06 m.s-1) and G2 (1.17 ± 0.08 and 1.07 ± 0.06 m.s-1). CS and SSO were higher in G1 than G2. There was no difference between SRCS and SRS30 in G1 (33.07 ± 4.34 and 31.38 ± 4.15 cycles.min-1) and G2 (35.57 ± 6.52 and 33.54 ± 5.89 cycles.min-1). In conclusion, SRCS can be used to predict the SRS30 irrespectively of the aerobic performance level.